A Narrative Inquiry of Students Translation Specialization Class’ Emotion in Translating Text - Weningtyas Dwi Astuti; Giyoto (Journal of Applied Linguistics, 2025)
This research studied about emotions that experienced by students of translation specialization class. The objective of this research was to explore the feeling and emotions of the students when they were translating text from their client. Researcher used narrative inquiry as the methodology in this research. Participants were students of English Language Education who were still receiving the project of translating text. The researcher used Emotional Geographies theory by Hargreaves (2001) to analyze the emotions of the participants. There were five points of emotional geographies proposed by Hargreaves: physical geography, moral geography, sociocultural geography, professional geography, political geography. The technique of collecting data from this research were observation and interview. The data were taken from participants’ utterances that transcribed by researcher. Researcher used Barkhuizen’s trustworthiness to reach validation of the data and minimize the bias by crosschecking data. Research findings showed that almost all participants felt the three themes of comfortable, neutral, and uncomfortable when they became students of translation specialization class. In this research, participants really felt the impact of activity restrictions. This affected their emotions when translating the text, they cannot meet directly with partner in translation agency or clients. Online communication caused some miscommunication, this can be resolved by several participants. However, this actually causes concern for other participants. Keywords : Narrative inquiry; translation specialization class; emotional geography.